The right to higher education : beyond widening participation - Burke, Penny Jane. (London : Routledge, 2012)
"The landscape of higher education has undergone change and transformation in recent years, partly as a result of diversification and massification. However, persistent patterns of under-representation continue to perplex policy-makers and practitioners, raising questions about current strategies, policies and approaches to widening participation. Presenting a comprehensive review and critique of contemporary widening participation policy and practice, Penny Burke interrogates the underpinning assumptions, values and perspectives shaping current concepts and understandings of widening participation. She draws on a range of perspectives within the field of the sociology of education - including feminist post-structuralism, critical pedagogy and policy sociology - to examine the ways in which wider societal inequalities and misrecognitions, which are related to difference and diversity, present particular challenges for the project to widen participation in higher education. In particular, the book: - focuses on the themes of difference and diversity to shed light on the operations of inequalities and the politics of access and participation both in terms of national and institutional policy and at the level of student and practitioner experience. - draws on the insights of the sociology of education to consider not only the patterns of under-representation in higher education but also the politics of mis-representation, critiquing key discourses of widening participation. - interrogates assumptions behind WP policy and discourse, including assumptions about education as an unassailable good and critically reflecting on what is meant by educational participation"--
pt. 1. Contextualizing and theorizing widening participation -- pt. 2. Methodologies and approaches -- pt. 3. Widening participation strategies and practices -- pt. 4. Imagining the future.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Educational equalization -- United States; Education, Higher; Education, Higher -- Aims and objectives; College attendance; Education and state; Right to education; Educational sociology; Electronic books